Huangqi-Honghua Combination Prevents Cerebral Infarction with Qi Deficiency and Blood Stasis Syndrome in Rats by the Autophagy Pathway. (24th January 2022) - Chen, Yue; Lei, Lu; Wang, Kai; Liang, Ruimin; Qiao, Yi; Feng, Zhijun; Zhang, Juanli; Bai, Min; Chen, Haixia; Zhao, Jiaxin; Xiong, Xingzhao; Cao, Jinyi; et al.
Abstract : Background . Cerebral ischemia/reperfusion injury (CI/RI) contributes to the process of autophagy. Huangqi-Honghua combination (HQ-HH) is a traditional Chinese medicine (TCM) combination that has been widely used in the treatment of cerebrovascular diseases in China. The role of autophagy in HQ-HH-mediated treatment of CI/RI is unclear. Methods . Sprague-Dawley (SD) rats were used to establish the middle cerebral artery occlusion (MCAO) with QDBS syndrome model and evaluate the function of HQ-HH in protecting against CI/RI. Results . HQ-HH significantly improved the neuronal pathology and reduced infarct volume, neurological deficits, and whole blood viscosity in rats with CI/RI. Western blot results showed that the expression of autophagy marker proteins LC3II/LC3I and Beclin1 in the HQ-HH group was significantly lower than that in the model group, while the expression of p62 was significantly higher in the HQ-HH group as compared with the model group. There were no significant differences in PI3K, Akt, and mTOR levels between the HQ-HH group and the model group; however, p-PI3K, p-Akt, and p-mTOR were significantly upregulated. In addition, HQ-HH also changed the composition and function of intestinal flora in MCAO + QDBS model rats. Conclusion . HQ-HH protects from CI/RI, and its underlying mechanism may involve the activation of the PI3K-Akt-mTOR signaling pathway, relating to the changes in the composition of intestinal flora.